Compounding Issues on the Translation of Drama/Theatre Texts - Che Suh, Joseph (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThis paper examines the main streams and players in the area of drama/theatre translation and highlights some of the issues involved in the translation of drama/theatre texts.